THE INFLUENCE OF COMMUNICATION, REWARDS AND PUNISHMENT ON EMPLOYEE PERFORMANCE AT PT. JAKARTA TECHNOLOGY MAIN MEDAN BRANCH - Yehezkiel Leonardo P Sitorus; Tri Yuni Sari Sinisuka; Devi Eliana Damanik; Syalom Triyosefin Lumban Toruan; Cut Fitri Rostina; Fauzi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to test and analyze the influence of communication, rewards and punishment on employee performance at PT. Jakarta Utama Technology Medan Branch. The population in this study is the number of employees at PT. Jakarta TeiMain Technology Medan Branch, beilocated on Jl. Sisingamangaraja KM 6.5 No.1, Simpang Marendal (Samping Indogrosir) Harjosari 1, Medan Amplas, North Sumatra, totaling 50 people and the sample used in this research was a saturated sample totaling 30 respondents fromicompany similar to employees of PT. Puninar Anji NYK Logistics Indonesia. Methodi used in this research is a quantitative approach. The data analysis technique in this research is through interviews and questionnairesir, and literature study. The results of this research show that communication has a positive and significant effect on kineiemployee work, and rewards have a positive and significant effect on employee performance, and punishment also has a negative and significant effect on employee performance. The results of the F test state that the communication, reward and punishment variables have a positive and significant effect on the variablesil employee performance. And the coefficient of determination R² is 52.3% and the remaining 47.7% is influenced by other variables not examined in this research.